2018
DOI: 10.3233/blc-170133
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Role of the Change in Neutrophil-to-Lymphocyte Ratio During Neoadjuvant Chemotherapy in Patients with Muscle-Invasive Bladder Cancer: A Retrospective, Multi-Institutional Study

Abstract: Background:The impact of the change in the neutrophil-to-lymphocyte ratio (NLR) during neoadjuvant chemotherapy (NAC) on outcomes in patients with muscle-invasive bladder cancer (MIBC) is poorly understood.Objective:To evaluate the prognostic impact of the change in NLR during NAC for patients with MIBC.Methods:Patients referred to academic, community, and quaternary referral centres in Alberta, Canada from 2005 to 2015, Ontario, Canada from 2005 to 2013, and Southampton, UK from 2004 to 2010 were evaluated. 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Salim et al also reported that the NLR is an independent prognostic factor in patients with recurrent or metastatic HNSCC . On the other hand, previous studies suggested that the NLR predicts chemotherapy outcomes in patients with various types of cancer . Although the clinical benefit (SD + PR) were observed in some of the patients with pretreatment NLR of ≥5.0 as well as in patients with pretreatment NLR of <5.0, pretreatment NLR ≥5.0 is associated with worse survival in patients undergoing nivolumab monotherapy in this study.…”
Section: Discussionmentioning
confidence: 42%
“…Salim et al also reported that the NLR is an independent prognostic factor in patients with recurrent or metastatic HNSCC . On the other hand, previous studies suggested that the NLR predicts chemotherapy outcomes in patients with various types of cancer . Although the clinical benefit (SD + PR) were observed in some of the patients with pretreatment NLR of ≥5.0 as well as in patients with pretreatment NLR of <5.0, pretreatment NLR ≥5.0 is associated with worse survival in patients undergoing nivolumab monotherapy in this study.…”
Section: Discussionmentioning
confidence: 42%
“…In MIBC (3), patients with high CRP before surgery have a significant correlation with adverse outcomes in treatment outcomes and survival. And NLR was relatively low in complete response and pathologic T0 in patients with high NLR before RC or before NAC (47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). And increased NLR levels during 1-3 months post RC were associated with adverse survival outcomes (12).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on the prognostic role of NLR in MIBC and metastatic BC ( Table 2) (24,41,(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). Furthermore, several studies have reported on the role of prognostic factors in survival outcomes of MIBC and metastatic UC (24, 41, 47, 48, 50, 52-56, 59, 60), while other studies have suggested that the postoperative stages or disease severity can be predicted (Table 3) (41,48,49,58,(69)(70)(71)(72)(73).…”
Section: Neutrophil-to-lymphocyte Ratiomentioning
confidence: 99%
“…In addition to local immunity, the peripheral absolute lymphocyte count has been associated with an inferior outcome in various cancers. 19 Furthermore, peripheral NLR has been postulated to be a prognostic factor for individuals with MIBC [26][27][28] and higher values of NLR have been associated with an increased risk of disease recurrence and overall survival in NMIBC. 29,30 In the present study and consistent with a recently published report, 39 a higher NLR prior to BCG treatment value was identified in BCG nonresponders, although the difference did not reach significance.…”
Section: Discussionmentioning
confidence: 99%
“…20 Furthermore, the neutrophil-to-lymphocyte ratio (NLR), a measure of systemic inflammation and a strong predictor for prognosis in patients with different diseases, 21,22 has been suggested to be a prognostic predictor for overall survival and disease free survival and a predictive marker of the response to treatment in many cancers. 23 In bladder cancer, high NLR has been associated with poor clinical outcome in individuals with muscle-invasive bladder cancer (MIBC), 24,25 it has been postulated as a prognostic factor for individuals with MIBC undergoing neoadjuvant chemotherapy [26][27][28] and it correlates with disease progression and recurrence in individuals with NMIBC. 29,30 Overall, immune biomarkers based on TILs or blood cells have been independently described in cancer patients; however, the possibility that a combination of both factors could generate a more reliable prognostic biomarker has not previously been explored.…”
Section: Introductionmentioning
confidence: 99%